THE IMPROVE SMALL AND MEDIUM ENTERPRISES PERFORMANCE WITH HOLISTIC MARKETING MODELS - Muksin, Abdullah (Dinasti International Journal of Management Science, 2021)
This study focuses on improving the performance of SMEs after using a holistic marketing model in their business. The unit of analysis in this research is UKM players who live in Bekasi, West Java. Hypothesis testing with path analysis and using SEM and Lisrel 8.80 software. This study produces a holistic marketing model that is effective, easy to understand and use to improve Small and Medium Enterprises in Indonesia. The results of this study prove that Relations Marketing has a positive and significant effect on the performance of SMEs, especially in building relationships with distributors. Integrated marketing has a negative and insignificant effect on the performance of SMEs, internal marketing has a positive but insignificant effect on the performance of SMEs, while Performance Marketing has a positive and significant effect on the performance of SMEs. Taken together, the holistic marketing model (relations marketing, integrated marketing, internal marketing, performance marketing) has a positive and significant effect on the performance of SMEs. The dominant variable affecting the performance of SMEs is Relations marketing.